Mini-DMEK for the Treatment of Chronic Focal Corneal Endothelial Decompensation. Issue 1 (4th January 2023) - Händel, Alexander; Siebelmann, Sebastian; Matthaei, Mario; Cursiefen, Claus; Bachmann, Björn
Abstract : Purpose: The purpose of the study was to evaluate the feasibility of mini-descemet membrane endothelial keratoplasty ("Mini-DMEK, " graft diameter <5 mm) for the treatment of chronic focal corneal endothelial decompensation for reasons other than acute hydrops in patients with keratoconus. Methods: Of the 3010 patients registered in the prospective Cologne DMEK database, 16 patients with focal corneal endothelial decompensation treated with Mini-DMEK were identified. After exclusion of patients with acute hydrops in keratoconus (n = 9), indications for focal corneal endothelial decompensation were either defects in Descemet membrane after intraocular surgeries (n = 5) or corneal edema in the area of Haab striae in buphthalmus (n = 2). Best spectacle-corrected visual acuity, corneal thickness in the affected area, and rebubbling rates served as main outcome measures. Results: All patients showed a postoperative increase in the best spectacle-corrected visual acuity from preoperative logarithm of the minimum angle of resolution (logMAR) 1.1 (±0.7) to logMAR 0.3 (±0.2) after the first month ( P = 0.046) and to logMAR 0.3 (±0.2) after half a year (5–7 months) ( P = 0.025). The corneal thickness decreased from preoperative 757 μm (±125) to 603 μm (±121) after the first month ( P = 0.031) and to 593 μm (±131) after half a year (5–7 months) ( P = 0.031). Rebubbling was necessary in 43% of patients (3 of 7 eyes). In 2 patients, Mini-DMEK was performed as triple Mini-DMEK including cataract surgery. Conclusions: Mini-DMEK is an effective treatment option for focal chronic corneal endothelial decompensation caused by tears in Descemet membrane or other defects such as Haab striae. Mini-DMEK can also be performed as a triple procedure including cataract surgery (triple Mini-DMEK).